TOXICITY OF METHOXYCHLOR AGAINST THE ONTOGENY OF RICE MOTH CORCYRA CEPHALONICA STAINT. (LEPIDOPTERA : PYRALIDAE) - TWARI, S.K.; BHATT, R.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1994)
Laboratory studies on the larvicidal and pupicidal effects of methoxychlor were made on the third instar larvae of Corcyra cephalonica Staint. It was observed that 0.016% (a.i.) w/w concentration of methoxychlor caused 100% larval death indicating absolute toxicity to the pest.